Competences of Community Health Care Management among Nursing Students of Boromarajonani College of Nursing, Ratchaburi - Patcheep, Kamonporn; Wongsawang, Nongnuch; Jongphae, Suriya; Boonsiri, Chonticha (Journal of The Royal Thai Army Nurses, 2021)
The purposes of this descriptive research were to identify and compare the respondents’ opinions towards competences of community health care management among nursing students. The participants were 143 nursing students, year 4, academic year 2018, 9 nursing instructors, and 9 preceptors. The research tool was a rating scale questionnaire, and it consisted of 3 aspects of competences of community health care management as follows: knowledge, attitude, and skill. The Cronbach’s Alpha Coefficient of the questionnaire was .97. The data was analyzed by using frequency, percentage, mean, standard deviation, The results showed that, among the respondents, the highest mean score was the preceptors’ opinion towards competences of community health care management among nursing students at a “good” level ( = 4.24, SD = .37). It was followed by the nursing students’ opinion and the nursing instructors’ opinion with a mean score of 4.10 (SD = .32) and 4.16 (SD = .42) at a “good” level, respectively. When considering each aspect, it was found that attitude aspect had the highest mean score, followed by skill, and knowledge in all participant groups. The comparison between groups of participants had a statistically significant difference for at least 1 pair of groups (F2,426 = 5.583, P = .004). Moreover, the preceptors’ opinion towards competences of community health care management among nursing students had a statistically significant difference from nursing instructors’ opinion (p≤.05)